The importance of defined-benefit occupational pension schemes in selected OECD countries - Frank Eich (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2010)
This paper discusses the role which (funded) defined benefit private sector occupational pension schemes play in national pensions in a sub-group of OECD countries. The paper shows that in the majority of countries under consideration statutory (state) pension schemes are the main if not only source of income in retirement for most people, with occupational pensions only playing at most a minor role. In several countries private sector occupational pension schemes do play an important role in providing pensioner incomes though. In these countries there has generally been a shift from DB to DC pensions, with the risks associated with pensions moved from businesses to individuals. Australia, for example, shifted from DB to compulsory DC pensions a generation ago, leaving only a few major businesses with any sizeable DB pension liabilities now. The US has undergone a similar shift though there is no compulsion. In the UK the economic and financial crisis has accelerated the closure of existing DB pension schemes and dealing with the legacy of DB pension liabilities is becoming a major issue. The picture is similar in the Netherlands and Ireland. The paper also shows the diverging DB arrangements in the private and public sectors, with governments in a number of countries continuing to offer (unfunded) DB pension promises when they have become less popular in the private sector.
Keywords: 330; Defined benefit pensions; Pension systems; State pensions; Pension funds; Pension liabilities